Depressive symptoms among Olympic athletes during the Covid-19 pandemic - Christophe Lambert; Lisa-Marie Schuetz; Simon Rice; Rosemary Purcell; Theresa Stoll; Martyna Trajdos; Ramona Ritzmann; Anna-Lena Böhm; Martin Walz (BMC, 2022)
Abstract Objectives The aim of this study was to analyze athlete-specific psychological strain among Olympic athletes following the postponement of the Tokyo 2020 Olympic games due to the COVID-19 pandemic. Methods A survey that comprised three sub-sections (Psychological Strain Questionnaire (APSQ), Patient Health Questionnaire-Depression Module (PHQ-8) and Participant characteristic) concerning mental health, performance issues and concerns about the postponement of the Tokyo Olympics, was distributed online and sent to 102 Olympic athletes. Results A total of 85 participants from 11 Olympic sports were enrolled. Results indicated that most athletes showed psychological strain related to concerns regarding the postponement of the Tokyo Olympics. Depression severity was positively associated with maladaptive avoidance coping patterns, negative effects in training, worries and fear. Depression severity was also negatively associated with motivation and adaptive factors such as chances and opportunities that can be drawn from the pandemic. Conclusion The present sample of Olympic athletes reported suffering from psychological uncertainty associated with the postponement of the Olympic games. Sports federations should therefore, provide ongoing wellbeing support to athletes and offer them, for example, sports psychological support in order to be able to better deal with pandemic-related uncertainties and changes.